Patterns of resident health workforce turnover and retention in remote communities of the Northern Territory of Australia, 2013-2015 - Deborah J Russell; Yuejen Zhao; Steven Guthridge; Mark Ramjan; Michael P Jones; John S Humphreys; John Wakerman (BMC, 2017)
Abstract Background The geographical maldistribution of the health workforce is a persisting global issue linked to inequitable access to health services and poorer health outcomes for rural and remote populations. In the Northern Territory (NT), anecdotal reports suggest that the primary care workforce in remote Aboriginal communities is characterised by high turnover, low stability and high use of temporary staffing; however, there is a lack of reliable information to guide workforce policy improvements. This study quantifies current turnover and retention in remote NT communities and investigates correlations between turnover and retention metrics and health service/community characteristics. Methods This study used the NT Department of Health 2013-2015 payroll and financial datasets for resident health workforce in 53 remote primary care clinics. Main outcome measures include annual turnover rates, annual stability rates, 12-month survival probabilities and median survival. Results At any time point, the clinics had a median of 2.0 nurses, 0.6 Aboriginal health practitioners (AHPs), 2.2 other employees and 0.4 additional agency-employed nurses. Mean annual turnover rates for nurses and AHPs combined were extremely high, irrespective of whether turnover was defined as no longer working in any remote clinic (66%) or no longer working at a specific remote clinic (128%). Stability rates were low, and only 20% of nurses and AHPs remain working at a specific remote clinic 12 months after commencing. Half left within 4 months. Nurse and AHP turnover correlated with other workforce measures. However, there was little correlation between most workforce metrics and health service characteristics. Conclusions NT Government-funded remote clinics are small, experience very high staff turnover and make considerable use of agency nurses. These staffing patterns, also found in remote settings elsewhere in Australia and globally, not only incur higher direct costs for service provision-and therefore may compromise long-term sustainability-but also are almost certainly contributing to sub-optimal continuity of care, compromised health outcomes and poorer levels of staff safety. To address these deficiencies, it is imperative that investments in implementing, adequately resourcing and evaluating staffing models which stabilise the remote primary care workforce occur as a matter of priority.